Clinical and Maternal Factors Predicting Length of Stay in Very Low Birth Weight Neonates: A Prospective Cross-Sectional Study from a Tertiary Care Center in Western India - Kilawat, Balmukund. R.; Rajan, Allampalam Raman; Jadhav, Shridhar; Rathod, Amit (Journal of Neonatal Surgery, 2025)
Background: Very low birth weight (VLBW) infants require specialized neonatal intensive care, resulting in prolonged hospitalization and increased healthcare costs. Understanding factors that predict length of stay (LOS) is crucial for resource planning and family counseling. Objective: To determine factors predicting length of stay in VLBW neonates in an urban tertiary care center in Western India. Methods: This prospective cross-sectional study enrolled 58 VLBW neonates (1000-1500g) admitted to a tertiary care NICU over an 18-month period. Maternal factors, neonatal characteristics, morbidities, and interventions were recorded. Length of stay and post-discharge outcomes were analyzed. Parametric data were evaluated using linear correlation, while non-parametric data were analyzed using Mann-Whitney U and Kruskal-Wallis tests. Results: Mean gestational age was 31.2±2.0 weeks and mean birth weight was 1284.2±137.8g. Mean LOS was 38.0±16.0 days (range: 9-73 days). Gestational age (r=-0.635, p<0.0001) and birth weight (r=-0.558, p<0.0001) showed strong negative correlations with LOS. Clinical sepsis (41.7±15.2 vs 22.2±7.8 days, p<0.0001), respiratory distress syndrome (44.7±14.8 vs 27.1±11.4 days, p<0.0001), apnea (43.3±14.5 vs 33.1±16.0 days, p=0.014), and intraventricular hemorrhage (73.0 vs 37.4±15.4 days, p=0.026) were associated with significantly longer LOS. Small for gestational age neonates had shorter LOS compared to appropriate-for-gestational-age counterparts (31.5±14.3 vs 40.7±16.1 days, p=0.046). Days to achieve full enteral feeding strongly correlated with LOS (r=0.604, p<0.0001). The overall mortality rate was 6.9% and readmission rate was 1.7%. Conclusion: Gestational age, birth weight, presence of sepsis, respiratory morbidities, and time to full enteral feeding were the strongest predictors of NICU length of stay in VLBW neonates. These findings can guide resource allocation, parental counseling, and development of interventions targeting modifiable factors to potentially reduce hospitalization duration without compromising outcomes